Productos turísticos y Patrimonio alimentario en el cantón Guano, provincia de Chimborazo - Moreira Chele, Kevin Geovanny (2024)
The research project was carried out in the canton of Guano in the province of Chimborazo with the aim of determining whether there is a relationship between the tourist product and the food heritage. The project was carried out using an inductive-deductive, analytic-synthetic approach, and the type of research was transversal, not experimental. Finally, the research design was based on the following approaches: documentary, field, descriptive and correlational. To obtain information, evaluation tools were used to assess reliability; two Likert-scale questions surveys were conducted to the managers of food and beverage establishments together with the authorities of the municipality of the canton of Guano. The Chi-Quadrat hypothesis test was used to evaluate the relationship between the study variables. The Chi-Quadrat hypothesis test was used to evaluate the relationship between the study variables. It was concluded that the tourist product is not related to the food heritage, since the lack of awareness about the gastronomic value has led to a weak promotion as part of the tourism offer, with the consequence, the limited dissemination of information for the development of tourist products, that is why the results obtained were also taken as reference and the proposal called “Strategies for the strengthening of tourism products, based on the food Heritage in the canton of Guano” was designed with the aim of consolidating clear ideas for the design of a tourism product that benefits the population, the managers of the food establishments and the tourists visiting the canton.